Will precision medicine be available for all patients in the near future?. Issue 1 (February 2019) - Gómez, René Maximiliano; Ansotegui, Ignacio; Canonica, Giorgio W.
Abstract : Purpose of review: Evidence-based medicine and guidelines directing the diagnosis and treatment of patients are changing. General recommendations are moving towards an individual focus, where technology evolution allows identification of specific patterns and where 'one size fits all' no longer has a place. Recent findings: Emerging innovations on health technology include useful tools for individualizing patients' specific conditions and follow-up. There are several preventive initiatives that aim to reduce allergic disease development, but they have no generalizable and definitive results as yet. Both omics and molecular diagnosis have provided the basis for differentiating clusters of patients, both allowing prediction of severity and also indicating appropriate management. Here we discuss examples contributing to some specific conditions we are now facing. Summary: Precision medicine encompasses a personalized care of the patient, the prediction of a successful treatment, the potential prevention of a disease and its progression when present and the important active participation of the patient in the planning and guidance of the approach and management. Technology and medical innovations like omics and molecular diagnosis help for discriminating specific phenotypes/endotypes and the correct individualized interventions. The great challenge for implementing precision medicine will be the possibility of providing those advances to everyone at affordable costs. Conclusion: Technology and innovations in medicine are aimed to help all patients globally, providing evidence for particular conditions that need to be personally considered, involving the patient's decision while treating, predicting and preventing disease. Our aim should be to have precision medicine available everywhere at any time.